Genetic Heterogeneity and Ethno-historical Considerations of Burusho and Balti Tribes with Regard to ABO and Rh Blood Group Alleles - Mohammad Abdul Naeem, Mohammad Abdul Naeem; Jamal Waris, Jamal Waris (Journal of Rawalpindi Medical College, 2007)
regard to ABO and Rh group alleles of Burusho and Balti tribes of northern Pakistan in order to determine origin of these populations. Methods: A prospective study was conducted from November 2006 to January 2007 at Combined Military Hospital Gilgit in which a total of 4318 blood samples were taken for ABO and Rh D blood grouping. They comprised of 3210 samples taken from the Burusho and 1008 samples of the Balti population. The method of sampling was random. Genetic affinities and gene diversity of the two populations was determined in terms of genetic distancing analysis with regards to ABO and Rh loci. Results: The average ABO allele frequencies in the Burusho population were ABO*A (0.37) ABO*B (0.32) ABO*AB (0.02) and ABO*O (0.29). Similarly the average allele frequencies of Balti population were ABO*A (0.23) ABO*B (0.31) ABO*AB (0.09) and ABO*O (0.37). In Brusho alleles frequencies for D and d of the Rh group system were 0.942 and 0.0580, for Balti 0.950 and 0.500 respectively for the total data. There is a marked increase in the frequency of blood group gene A in Burusho population and a corresponding decrease in blood group gene O as we proceed from older to younger age groups. Also there is significant divergence (p <0.05) in Burusho population for the distribution of ABO alleles from the general South Asiatic trend (O greater than B greater than A). Probably because of the relatively small starting value of r < 0.5 a selection took place against group O resulting in an increase of the blood group gene A in Burusho population. Conclusion: The genetic distance analysis reveals that the two tribes included in this study are genetically distant from one another and the genetic clustering pattern correlates with linguistic/ethnic affiliation and geographical proximity of these tribal populations to a certain extent.